2007
DOI: 10.1086/522147
|View full text |Cite
|
Sign up to set email alerts
|

CD14 C(−159)T Polymorphism Is a Risk Factor for Development of Pulmonary Tuberculosis

Abstract: No association between TLR4 Asp299Gly and pulmonary TB was found. CD14 -159TT is a risk factor for development of pulmonary TB, whereas mCD14/sCD14 and mTLR4 are possible biomarkers for the prognosis for TB disease. CLINICAL TRIAL PROTOCOL ID: SA1168-05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 47 publications
11
58
0
Order By: Relevance
“…Evaluation of the CD14 C(-159)T polymorphism showed that the TT genotype may be a risk factor for the development of TB. Similar results have been observed in a Mexican population (Rosas-Taraco et al, 2007). More studies are needed in other populations to confirm these results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Evaluation of the CD14 C(-159)T polymorphism showed that the TT genotype may be a risk factor for the development of TB. Similar results have been observed in a Mexican population (Rosas-Taraco et al, 2007). More studies are needed in other populations to confirm these results.…”
Section: Discussionsupporting
confidence: 88%
“…However, these authors found that the levels of mCD14/sCD14 in TB patients with the CD14-1145 GG genotype did not differ compared to other genotypes. Similar results were reported by Rosas-Taraco et al (2007) in a study of the CD14 C(-159)T polymorphism and development of pulmonary TB; although the CD14-159 TT genotype appeared to be a risk factor for TB, no differences were found between CD14-159 genotypes and the levels of either mCD14 or sCD14. These negative results may be due to the complexity of gene-environment interactions, which play an important role in microbial exposure and influence CD14 expression in TB patients and even in controls.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…21 It is interesting to note that the IBD5 haplotype is distributed differently in Asian and European populations, and that the IBD5 risk haplotype in Europeans is very rare in Asians. 22 Although candidate genes including IL4 23 and CD14 24,25 have been studied in this particular region, roles of these genes in tuberculosis remain inconclusive. Small sample size and ethnicity of the study populations may partially explain these equivocal association results.…”
Section: Discussionmentioning
confidence: 99%
“…MD-2 knockout mice were reported to have increased resistance to endotoxemia but increased susceptibility to Salmonella typhimurium infection (Nagai et al, 2002). So far, several polymorphisms in the genes encoding CD14 and TLR4 have been considered to determine susceptibility to TB (Pacheco et al, 2004;Ferwerda et al, 2007;Rosas-Taraco et al, 2007). In view of the functional significance of genetic polymorphisms in CD14 and TLR4 genes, and their close relationship with MD-2, we hypothesized that certain polymorphisms in the MD-2 gene may also influence the development of TB.…”
Section: Introductionmentioning
confidence: 99%